Exploring RNF213 in Ischemic Stroke and Moyamoya Disease: From Cellular Models to Clinical Insights - Benjamin Y. Q. Tan; Charlene H. P. Kok; Megan B. J. Ng; Shaun Loong; Eric Jou; Leonard L. L. Yeo; Weiping Han; Christopher D. Anderson; Chiea Chuen Khor; Poh San Lai (Biomedicines)
Advances in stroke genetics have highlighted the critical role of rare genetic variants in cerebrovascular diseases, with RNF213 emerging as a key player in ischemic stroke and Moyamoya disease (MMD). Initially identified as the primary susceptibility gene for MMD, RNF213—notably the p.R4810K variant—has been strongly linked to intracranial artery stenosis (ICAS) and various ischemic stroke subtypes, particularly in East Asian populations. This gene encodes an E3 ubiquitin ligase with diverse roles in angiogenesis, vascular remodeling, lipid metabolism, and cerebral blood flow regulation, yet its exact mechanisms in cerebrovascular pathology remain incompletely understood. This review synthesizes findings from genetic studies, as well as cellular and animal models, to provide a holistic understanding of RNF213’s involvement in cerebrovascular diseases. Key mechanisms by which RNF213 variants contribute to disease pathogenesis are explored, alongside discussions on their clinical utility as biomarkers and therapeutic targets. Additionally, we address the gene’s implications for disease prediction, risk assessment, and cascade screening. By integrating evidence across disciplines, this review identifies critical knowledge gaps, including the biological pathways underlying RNF213’s pathogenicity. These insights lay the groundwork for future research and underscore the potential of RNF213 in driving personalized approaches to cerebrovascular disease management.